Penggunaan Teknik Shaping dan Reinforcment untuk Mengatasi Perilaku Picky Eater Tidak Mengkonsumsi Sayuran Pada Anak Usia Sekolah - Annisa Humaira; Rhezandya Pradiptha Zalma; Saskia Ramadhani; Nurul Aulia; Melly Yuliani (PT. Giat Konseling Nusantara, 2025)
Nutrition is said to be balanced when the food consumed contains nutrients of the kind and quantity (portions) according to need. However, it is proven that as many as 83.64% of school-age children in Indonesia are still under-consuming vegetables. Still a lot of kids have picky-eater behavior especially in vegetable consumption. This picky-eater behavior has been targeted for intervention in A, a 10-year-old boy. Based on preliminary studies, A doesn't like to eat vegetables except salad vegetables. This single-subject study aims to look at the effectiveness of applying shaping and reinforcement techniques in increasing the frequency of vegetable intake in children suffering from picky eater.